Implementasi strategi bahasa indonesia dalam membangun kesadaran identitas dan jati diri bangsa di tengah dinamika global - Kurnianingsih, Riyadhotul (Maliki Interdisciplinary Journal, 2025)
Indonesian has been an integral part of Indonesia’s national identity and is deeply embedded in people’s lives for a long time. As a cultural heritage and unifying tool, Indonesian reflects the values of togetherness, unity, and distinctive national identity. In the context of strengthening national identity, this language acts as the main pillar that maintains the unity and integrity of the nation, despite facing the challenges of globalization and changing times that can threaten the preservation of national linguistic and cultural values. This research highlights the importance of preserving Indonesian as a local wisdom that not only functions as an element of communication, but also as a basis for social, economic and political development in Indonesia. The role of the younger generation is crucial in internalizing and reviving the use of Bahasa Indonesia so that this language remains relevant and becomes a strong foundation for Indonesia’s national identity.